Morphological and biometric features of preexisting posterior capsule defect in congenital cataract. Issue 7 (July 2018) - Li, Zhangliang; Chang, Pingjun; Wang, Dandan; Zhao, Yinying; Hu, Man; Ding, Xixia; Yu, Liuqing; Zhao, Yune
Abstract : Purpose : To describe the diagnostic signs and biometric characteristics of preexisting posterior capsule defects in congenital cataract. Setting : Eye Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, China. Design : Retrospective case series. Methods : Eyes with congenital cataract were reviewed and divided into a preexisting posterior capsule defect group (study group) and a control group with intact posterior capsules. Diagnostic signs were summarized on agreement of 3 ophthalmologists after they reviewed surgical videos. The biometric parameters, including central corneal thickness, anterior chamber depth, lens thickness, vitreous chamber depth, axial length, mean keratometry, corneal astigmatism, corneal diameter, and intraocular pressure, were compared between groups. The predictors of preexisting posterior capsule defect were determined using univariate and multivariate analyses. Results : The study comprised 81 eyes (53 patients). The diagnostic signs of preexisting posterior capsule defect included posterior capsule plaque with a well‐demarcated margin, gray granules and vacuoles, and heterogeneous nuclear opacity (more dense in the posterior). The lens was significantly thinner in the study group than in the control group ( P < .001). The corneal diameter was significantly smaller in the study group ( P = .015 horizontal and P = .005 vertical). Multivariate analysis identified lens thickness as an independent predictor (odds ratio, 0.731; 95% confidence interval, 0.621‐0.860; P < .001). Conclusions : For preexisting posterior capsule defect, lens thickness was a valuable predictor and the presence of characteristic morphology was an important indicator. The cornea configuration suggests the need for further study of the role of genetic mutation.